Determinants Affecting Audit Delay in Companies on the Indonesia Stock Exchange for the 2019-2021 Period - Wandira, Putri Ayu; Pratiwi, Wiwik (Journal of International Conference Proceedings, 2023)
This study was conducted to determine the correlation between profitability, Company age, and auditor's opinion on partial or simultaneous audit delays in food and beverage industry companies listed on the Indonesia Stock Exchange for the period 2019-2021. The following is a list of National Register of Historic Places listings in Fort Worth County (idx.co.id). samples were selected by purposive sampling technique and obtained 17 companies. The Data were processed using quantitative methods, and software program eviews 12.0, tested and analyzed by classical assumption test, panel data regression, and hypothesis test. The results showed that the variable profitability, age of the company, and the opinion of the auditor partially and simultaneously have a negative and significant effect on audit delay. Novelty of this study is the research period, research variables, research targets and treatment in sample selection. The research implication is that companies that are able to suppress audit delay figures can use funds optimally, and are able to attract the attention of investors. This has an impact on economic growth because it can recover faster and stronger.Keywords: Age of The Company, Audit Delay, Auditor Opinion, Profitability